A study of size, growth and rationalization of the bureaucracy - Mangahas, Joel V. (1993)
The paper addresses the issue of "bloatedness" in the size of the Philippine bureaucracy. Using international comparisons, the paper suggests that the Philippine government is not as big as it is commonly perceived to be and that recent policy measures to trim and streamline the bureaucracy should be reconsidered and placed in proper context. For purposes of providing Philippine policymakers a useful case study, the paper introduces the process and policy content of administrative reform programs carried out in Japan to restrain government growth and to rationalize the administrative system. Determinants of government growth/reduction are likewise identified by utilizing correlation and regression tests.
Keywords: Administrative reform -- Japan; Bureaucracy -- Japan; Bureaucracy -- Philippines